Wartime Violence and Post-conflict Situation: The Nepalese Experience - Aryal, Gajendra (Kathmandu School of Law Review, 2018)
The end of the war is about the restoration of peace, law and order, and respect for human rights including improvement of the socio-economic situation of the country. Providing justice to the victims of war in the post-conflict situation is very challenging. It may take years to recover wounds of war victims. The attempt of conflict settlement mostly depends upon the will and skill of the government. Unlike this, the Nepalese government is not so far rigorously engaged for justice delivery to the wartime victims. Even after the resolution of conflict, there are many tough political agendas and many serious issues to address. Furthermore, the country was witnessing total restructuration from base to the superstructure. Still, minor ethnic skirmishes in the Terai region of the country were broken out. Many dissatisfied and disgruntled groups raised different types of voices of dissonance. As a result, the government had to act with prudence to tackle those issues. In the government’s involvement in addressing those issues like pragmatic challenges of restructuration, ethnic upsurge and Madhesi movement, less attention was given by the government to work for redressing, allaying and soothing the lingering vestige of a war crime, trauma and pangs of displacement. Even in the transitional phase, none of the strong redemptive measures were taken to cope with the lingering impact of wartime crime, traumatic onslaught and the prolonged effect of getting exposed to violence in the past. Due to the political instability in the country and lack of political consensus between major political parties, less attention has been paid to people’s sufferings and pains. Psychosocial rehabilitation has been a neglected issue in post-conflict reconstruction. People have gone through multiple aspects of war violence impacts, displacement, and traumatic experiences in the post-conflict context. DOI: https://doi.org/10.46985/jms.v6i2.207